Experimental study of pressure effects on the thermal performance of trap pipes in a horizontal water-tube boiler - Kurniawan, Irwan; Burhan Hafid; Jumarizan; Maksum (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2026)
Boiler systems are widely used in industrial processes to convert fuel energy into thermal energy in the form of steam. Improving boiler thermal performance is essential to reduce fuel consumption, operating costs, and energy losses. One approach to enhance energy utilization is the recovery of residual heat from flue gases. In water-tube boilers, additional heat recovery components such as trap pipes can be installed along the flue gas path to capture unused thermal energy before it is discharged through the exhaust system. However, the thermal contribution of trap pipes in small-scale boilers operating at relatively low pressures has not been widely investigated. This study aims to experimentally evaluate the influence of operating pressure on the thermal performance of trap pipes installed in a horizontal water-tube boiler system. The experimental setup consists of a boiler with a water capacity of 588 liters fueled by waste oil. The trap pipe assembly includes 30 tubes with an outer diameter of 27 mm and a length of 398 mm, providing a total effective heat transfer area of 1.013 m². Experiments were conducted at operating pressures of 1, 2, 3, and 4 bar under steady-state conditions. Thermal performance was assessed using energy balance analysis to determine trap pipe efficiency, surface heat flux, and total heat loss. The results indicate that increasing operating pressure enhances the heat recovery capability of the trap pipe system. Trap pipe efficiency increased from 2.54% at 1 bar to 3.95% at 4 bar, while the surface heat flux showed a slight rise from approximately 16.75 kW/m² to 16.90 kW/m². Despite this improvement, total heat loss increased significantly with pressure due to higher fuel consumption and greater temperature gradients. These findings suggest that pressure elevation improves local heat transfer but also intensifies energy dissipation, indicating a thermodynamic trade-off in boiler operation